1978
DOI: 10.1139/x78-036
|View full text |Cite
|
Sign up to set email alerts
|

Container and root treatments affect growth and root form of planted ponderosa pine

Abstract: Field performance and root form of container-grown Pinnsponderosa Laws. seedlings were studied after application of three treatments and compared with untreated bare-root seedlings. One-year-old seedlings grown in 1.9-ℓ milk carton containers were treated by (1) removing the bottom of the container, (2) removing the whole container, and (3) removing the whole container and cutting spiralled roots off at the bottom of the surface of the root ball. Survival was excellent for trees of all treatments. Bare-root se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Not only had the container seedlings compensated for being significantly shorter initially, but they also had surpassed their bareroot counterparts . Owston and Seidel (1978) found that first-year height growth was best for bareroot ponderosa pine seedlings in Oregon, but after 5 years, the average height of container seedlings was greater. After 10 growing seasons, container seedlings generally were taller than bareroot seedlings .…”
Section: Resultsmentioning
confidence: 94%
“…Not only had the container seedlings compensated for being significantly shorter initially, but they also had surpassed their bareroot counterparts . Owston and Seidel (1978) found that first-year height growth was best for bareroot ponderosa pine seedlings in Oregon, but after 5 years, the average height of container seedlings was greater. After 10 growing seasons, container seedlings generally were taller than bareroot seedlings .…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, cutting roots of container-grown Pinus contorta vertically had no effect on percentage of acceptable seedlings for (Seaby and Schaible 2001). In other trials with no toppling, cutting roots reduced spiraling of roots (Persson 1978), improved the appearance of subsequent root growth (Bell 1978;Owston and Seidel 1978), and stimulated growth of geotropic sinker roots (Khurana 2001). Several root pruning trials have been conducted on container-grown pine seedlings.…”
Section: Cutting Rootsmentioning
confidence: 96%
“…Beginning in the late 1960s, field trials of container stock and comparisons with bare-root seedlings became part of the research effort. Early studies included a comparison of survival, growth, and root form of containerized Douglas-fir and noble fir (Owston and Stein 1978), how container and root treatments affected growth of ponderosa pine (Owston and Seidel 1978), and a regionwide effort to compare performance of bare-root and containerized seedlings (Owston 1990, Owston and. And, in British Columbia, the concerted effort to evaluate container seedling performance continued.…”
Section: Direct Seedingmentioning
confidence: 99%